1998
DOI: 10.1093/ortho/25.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Patient attitudes to glove use by orthodontists.

Abstract: The aim of this study was to evaluate the awareness of orthodontic patients of the importance of glove wearing by orthodontists, and consisted of a patient completed questionnaire carried out at an orthodontic clinic in Ireland. The subjects were 194 consecutive patients [122 (63 per cent) female, 72 (37 per cent) male; mean +/- SD age: 15.5 +/- 2.2 years] attending an orthodontic clinic. They completed a questionnaire designed to determine their attitudes to the wearing of gloves by orthodontists. Most patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In the previous studies, patients were of the opinion that glove usage will protect both the orthodontist and the patient (89.4% and 94%). 25,26 The results of this study indicate only 74% of patients thought that glove use will protect both orthodontists and patients. Ten percent of them believe that glove wear will protect the orthodontist only and 12% reported that glove wear will protect patients only.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…In the previous studies, patients were of the opinion that glove usage will protect both the orthodontist and the patient (89.4% and 94%). 25,26 The results of this study indicate only 74% of patients thought that glove use will protect both orthodontists and patients. Ten percent of them believe that glove wear will protect the orthodontist only and 12% reported that glove wear will protect patients only.…”
Section: Discussionmentioning
confidence: 85%
“…26 A comparatively high level (97%) of awareness was reported in Ireland. 25 In contrast a study on German orthodontists, showed that 16.9 percent of surveyed individuals considered wearing gloves was absolute necessary. 24 A high percentage (88%) of patients felt that they would not go to an orthodontist who didn't wear gloves; this coincided with the results of previous studies.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations